2016
DOI: 10.1111/hsc.12355
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants in the sexual health of adolescent Aboriginal Australians: a systematic review

Abstract: While research indicates that Aboriginal and Torres Strait Islander adolescents may be at increased risk of some sexually transmitted infections, there is limited information about factors that may place these young people at more risk of adverse sexual health than their non‐Indigenous counterparts. Current research has tended to focus on surveillance‐type data, but there is an increasing need to understand social determinants of sexual health risk. This systematic review assessed the evidence of social determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…85,90,91 Among Indigenous populations, legacies of mistreatment and forced dislocation from traditional lands, communities and culture likely played critical roles in giving rise to current structural determinants, including poverty, educational disadvantage, poor living conditions and barriers to accessing high-quality healthcare. [91][92][93][94][95][96][97] These factors in turn contribute to substance abuse and poor sexual health outcomes (young age of sexual debut, inconsistent condom use and multiple partners) among Indigenous youth. 97…”
Section: Racial and Ethnic Minorities And Indigenous Populationsmentioning
confidence: 99%
“…85,90,91 Among Indigenous populations, legacies of mistreatment and forced dislocation from traditional lands, communities and culture likely played critical roles in giving rise to current structural determinants, including poverty, educational disadvantage, poor living conditions and barriers to accessing high-quality healthcare. [91][92][93][94][95][96][97] These factors in turn contribute to substance abuse and poor sexual health outcomes (young age of sexual debut, inconsistent condom use and multiple partners) among Indigenous youth. 97…”
Section: Racial and Ethnic Minorities And Indigenous Populationsmentioning
confidence: 99%
“…Rigorous qualitative research can provide in-depth insight into the factors underlying findings identified in survey-based and epidemiological research [14]. Yet there exists a paucity of qualitative research examining sexual health among young Aboriginal Australians [15].…”
Section: Introductionmentioning
confidence: 99%
“…First, factors contributing to STIs among Aboriginal people living in remote areas include poorer outcomes in known determinants of health, such as education, health care access, income and employment . Second, age is a specific risk factor for STI transmission; only one‐third of non‐Indigenous Australians are aged under 25 years, compared with over half of Aboriginal people .…”
Section: Factors Affecting Sexually Transmissible Infections In Remotmentioning
confidence: 99%